2020
DOI: 10.1186/s12883-019-1582-1
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of lower urinary tract symptoms based on individual and clinical parameters in patients with multiple sclerosis

Abstract: Background: Most patients with multiple sclerosis (MS) suffer from bladder dysfunction during the course of the disease. This study was conducted to examine the prevalence of these complications among patients with MS. Methods: This cross-sectional study was performed on 602 patients with MS who referred to the neurology clinics of Kashani and Alzahra Hospitals affiliated to Isfahan University of Medical Sciences, Isfahan, Iran. Multistage random cluster sampling was performed and the informed consent form was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 38 publications
(56 reference statements)
0
14
2
2
Order By: Relevance
“…Pads are associated with an increase in economic burden in multiple sclerosis 34. In our study, no significant differences in pad usage were found between the Tele-PFMT and Home-PFMT groups.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Pads are associated with an increase in economic burden in multiple sclerosis 34. In our study, no significant differences in pad usage were found between the Tele-PFMT and Home-PFMT groups.…”
Section: Discussioncontrasting
confidence: 64%
“…Pads are associated with an increase in economic burden in multiple sclerosis. 34 In our study, no significant differ-ences in pad usage were found between the Tele-PFMT and Home-PFMT groups. On the other hand, both intervention groups were better than the control group in terms of pad usage.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…For example, a Canadian study found that males with MS had a higher relative prevalence of anxiety and depression than females at MS diagnosis ( 24 ). Further, an Iranian study found that lower urinary tract symptoms, such as intermittent urine stream, hesitancy and straining, were more common in males with MS, though relative comparisons were not made with general population controls ( 29 ). Studies have suggested that low testosterone levels are associated with increased MS risk and greater MS disability progression ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple Sclerosis (MS) is a chronic inflammatory disease of the CNS, affecting approximately 100,000 patients in the U.K. and 2,500,000 patients globally [59]. Interestingly, it can affect up to three times as many women as men, with an average age of onset in early adulthood [60].…”
Section: Multiple Sclerosismentioning
confidence: 99%